DFT and post-DFT studies of metallic MXY3-type compounds for low temperature TE applications. (October 2016) - Bilal, M.; Saifullah,; Ahmad, Iftikhar; Jalali-Asadabadi, S.; Ahmad, Rashid; Shafiq, M.
Abstract: In this paper, thermoelectric properties of carbon and nitrogen based twenty metallic antiperovskites MXY3 (M=Al, Ga, Ir, Mg, Pd, Pt, Rh; X=C, N; Y=Mn, Ni, Sc, Ti, Cr, Fe) using ab-initio density functional theory and post-DFT Boltzmann's techniques are investigated. The electronic properties of these compounds are also discussed. We find high values of Seebeck coefficient and small values of electronic thermal conductivity for AlCTi3, AlNSc3, AlCNi3, AlNTi3, GaCCr3 and MgCNi3 between −0.25 and 0.25 eV chemical potential. These results show high dimensionless figure of merit in metallic materials and therefore, we predict these materials can be potential candidates for low temperature thermoelectric applications. Highlights: Electronic and thermoelectric properties, against chemical potential, of twenty antiperovskites MXY3 (M=Al, Ga, Ir, Mg, Pd, Pt and Rh; X=C and N; Y=Mn, Ni, Sc, Ti, Cr and Fe) are investigated for the first time. We predict Seebeck coefficients of metallic AlNTi3 and AlCTi3 show highest values of 110 and 100 μV/K respectively, at room temperature. Small values of thermal conductivities are achieved for these materials which are suitable for thermoelectric applications. Figure of merit approaches to 0.32 and 0.25 for AlNTi3 and AlCTi3 respectively, which shows these materials can be useful for thermoelectric devices and alternative energy applications.